A Simple and Ligand‐Free Synthesis of Light and Durable Metal‐TiO2 Polymer Films with Enhanced Photocatalytic Properties. Issue 23 (10th November 2021) - Li, Xinyuan; Xu, Yikai; Greer, Adam J.; Yue, Mingjian; Ye, Ziwei; McNeill, Aaron; Li, Chunchun; Mills, Andrew; Hu, Peijun; Hardacre, Christopher; Bell, Steven E. J.
Abstract: The photocatalytic efficiency of TiO2 can be increased by using co‐catalysts, such as metal nanoparticles, which act as electron sinks to suppress the recombination of photogenerated electron–hole pairs. The main challenge in preparing such systems is to create intimate contact between the metal and the TiO2 surface while still maintaining control over the morphology and distribution of the metal nanoparticles in the TiO2 matrix. Here lightweight TiO2 films are prepared by assembling a layer of TiO2 nanoparticles onto a thin polymer support, followed by physical vapor deposition of metal nanoparticles onto the TiO2 surface. Importantly the fabrication does not involve any chemical modifications to the surface of NPs, which allows spontaneous formation of strong chemical bonds between deposited metal and TiO2 . Systematic optimization of this process gives materials 6× more catalytically active than the parent TiO2 films and up to 18× more catalytically active than commercial photoactive TiO2 glass. Moreover, the transparent, flexible, and robust polymer support enables the product films to be easily used for repeated photocatalytic reactions. Since the whole fabrication process is scalable and highly reproducible, this approach provides new opportunities for controlled synthesis of a new family of practical high‐performance metal‐ semiconductor hybrid photocatalysts. Abstract : Lightweight and flexible metal‐TiO2 ‐polystyrene films are synthesized through a ligand‐free process. This enables direct metal‐TiO2 contact giving rise to outstanding photocatalytic performance, 18× better than commercial TiO2 films.